2020
DOI: 10.1038/s41598-020-78276-4
|View full text |Cite
|
Sign up to set email alerts
|

Domain-specific functional coupling between dorsal and ventral systems during action perception

Abstract: Visual perception of actions and objects has been shown to activate different cortical systems: action perception system spanning more dorsally, across parietal, frontal, and dorsal temporal regions; object perception relying more strongly the ventral occipitotemporal cortex (VOTC). Compared to the well-established object-domain structure (e.g., faces vs. artifacts) in VOTC, it is less known whether the action perception system is constrained by similar domain principle and whether it communicates with the ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Future research would be needed to determine whether all event types can drive an NSW effect, or only social ones. Interestingly, some recent studies have suggested that some sub-regions in PLTC may favor the representation of social interactions over non-social ones ( Wurm et al, 2017 ; Wurm and Caramazza, 2019 ; Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future research would be needed to determine whether all event types can drive an NSW effect, or only social ones. Interestingly, some recent studies have suggested that some sub-regions in PLTC may favor the representation of social interactions over non-social ones ( Wurm et al, 2017 ; Wurm and Caramazza, 2019 ; Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…2021 ). In addition, the numerosity network showed dense connections between the left temporal and right premotor, and between the left temporal and right parietal sensorimotor regions, which may represent a functional coupling between the ventral and dorsal areas in the numerosity system ( Yang et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Events are typically constituted by actions and entities, which have been shown to be supported by (partly) different brain networks (e.g., Vigliocco et al 2011;Yang et al 2017). Intriguingly, domain-preferential representations both for actions (e.g., social/human-directed and manipulation/object-directed; Wurm et al 2017;Yang et al 2020) and objects (e.g., animate and inanimate; Bi et al 2016;Caramazza and Shelton 1998;Kanwisher 2010;Konkle and Caramazza 2013;Kriegeskorte et al 2008b) have been reported as a salient neural organization principle. Does the brain also respect this domain organization in event composition (e.g., social-person constructions such as "hug mother" or manipulation-artifact constructions such as "fold napkin")?…”
Section: Introductionmentioning
confidence: 99%